Achieving active distribution networks through operational and architectural aspects analysis: a methodology for long-term planning - Ulrich Ziegler, David; Prettico, Giuseppe; Mateo Domingo, Carlos; Gómez San Román, Tomás (My University, 2024)
To enable the paved energy transition towards a cleaner and more sustainable living substantial changes are required at the power distribution grid level. Distributed energy resources together with the emerging actors in the electricity sector (electric vehicles, storage systems, heat-pumps, etc.) offer the opportunity to accomplish this ambitious goal by minimizing at the same time the overall cost for society. Active Distribution Networks (ADN) are distribution networks with a high degree of automation that by enhancing their observability and controllability could fit the purpose. However, given the considerable number of technology options already available a thorough assessment of their advantage with respect to traditional methods mainly based on network expansion is still lacking. In this paper we propose a step-by-step methodology which aims at tackling the problem of efficiency in long term planning based on the ADN concept. To help clarify the key steps discussed in the proposed methodology the case study of a large-scale city network is shown. A first benchmark between the built ADN and the conventional expansion option is quantified and discussed in detail. Results show the potential of demand response to reduce distribution investment cost by 14 % and annual operational cost by 7% for conventional expansion in the analysed case study.